Effects of Nordic walking on physical functions and depression in frail people aged 70 years and above - Lee, Han Suk; Park, Jeung Hun (Journal of Physical Therapy Science, 2015)
[Purpose] This study investigated the effects of Nordic walking on physical functions and depression in frail people aged 70 years and above. [Subjects] Twenty frail elderly individuals ≥70 years old were assigned to either a Nordic walking group (n=8) or general exercise group (n=10). [Methods] The duration of intervention was equal in both groups (3 sessions/week for 12 weeks, 60 min/session). Physical function (balance, upper extremity strength, lower extremity strength, weakness) and depression were examined before and after the interventions. [Results] With the exception of upper extremity muscle strength, lower extremity strength, weakness, balance, and depression after Nordic walking demonstrated statistically significant improvement. However, in the general exercise group, only balance demonstrated a statistically significant improvement after the intervention. There were significant differences in the changes in lower extremity muscle strength, weakness and depression between the groups. [Conclusion] In conclusion, Nordic walking was more effective than general exercise. Therefore, we suggest that Nordic walking may be an attractive option for significant functional improvement in frail people over 70 years old.